Implementasi Pelaksanaan Ekstrakurikuler Wajib dan Pilihan SD Negeri dan SD Swasta di Kota Bandung (Penelitian Kualitatif terhadap SDN Negeri 172 Andir Kidul dan SD Bintang Madani) - Rachmi Nursifa Yahya; Fannia Sulistiani Putri; Andriani Safitri; Zizah, Silsi Nur; Mulyana, Agus (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
This study aims to see a comparison between extracurriculars implemented in public and private elementary schools. As for observations in the field, namely looking at comparisons regarding planning, implementation, and assessment of mandatory and optional extracurriculars. Researchers used 2 schools, namely 172 Andir Kulon Public Elementary School and Bintang Madani Elementary School located in the city of Bandung. This extracurricular aims to develop and train students' interests and skills outside of their academic abilities and carried out outside of school activities. The method used in this study is to use qualitative research. The methods used are interviews and field observations. The results of this study show that there are differences from the two schools. The difference looks significant starting from the planning, implementation, and extracurricular assessment.